Culture and Teacher Professional Identity: an exploration of identity construction among Native English Speaking Teachers in Brunei Darussalam. - Busko, James (2017)
Native English Speaking Teachers (NESTs) play a significant role within the education system in Brunei Darussalam (BDS), yet to date there appears to be no research until now which examines this body of teachers. By employing a sociological view to identity construction, this paper considers perceptions of culture and their relevance to teacher identity. Drawing on a nation-wide network of teachers, 80 NESTs in government schools in Brunei reflected upon culture, as they considered their own teacher identities. A comprehensive survey determined that culture plays important roles in terms of creating and maintaining identity among these NESTs in BDS. A strong sense of cultural identity for the majority of NESTs in this study plays dual roles. Firstly, it functions as the medium through which they interpret features of Bruneian culture. Secondly, it acts as a barrier, which prevents them from viewing Bruneian culture as a vehicle to gain a greater understanding of themselves, as well as improve their classroom pedagogy.